A Population-Based Survey to Determine Association of Perceived Social Support and Self-Efficacy With Self-Care Among Elderly With Diabetes Mellitus (Kerman City, Iran). (December 2017) - Borhaninejad, Vahidreza; Shati, Mohsen; Bhalla, Devender; Iranpour, Abedin; Fadayevatan, Reza
This survey examined association between social support and self-efficacy with self-care in elderly with diabetes. A total of 374 subjects were identified in Kerman city, Iran who responded to questionnaires on self-care, social support, and self-efficacy. Data were analyzed by using SPSS. Along with customary descriptive statistics, we also determined group difference for self-care, and Pearson correlation, and prediction value of various variables by using hierarchical multiple regression. And 67.37% of subjects were classified as poor adherence to self-care; 55.9% patients reportedly had good foot care habits, while 68.4% patients were not taking adequate physical activity. There was a significant correlation between self-care with social support and self-efficacy. Independent variables accounted for 44.3% of the variance in self-care. Diabetes care programs should aim to implement (a) weekly free-of-cost mass physical activity programs, (b) mass education adapted for gender- and age-based needs, and (c) informal social cohesion and companionship among general public.